Inflammasomes during SARS-CoV-2 infection and development of their corresponding inhibitors - Diarimalala, Rominah Onintsoa; Wei, Yanhong; Hu, Da; Hu, Kanghong (Frontiers in Cellular and Infection Microbiology, 2023)
COVID-19 continues to be a burden for human health since its outbreak in Wuhan, China in December 2019. In severe cases, SARS-CoV-2 provokes inappropriate hyperinflammatory immune responses leading to acute respiratory distress syndrome (ARDS) and even death. This process is regulated by inflammasomes which are activated after binding of the viral S protein to cellular angiotensin-converting enzyme 2 (ACE2) receptor and triggers innate immune responses. The formation of “cytokines storm” leads to tissue damage and organ failure. NOD-like receptor family pyrin domain containing 3 (NLRP3) is the best studied inflammasome known to be activated during virus infection. However, some studies suggest that SARS-CoV-2 infection is associated with other inflammasomes such as NLRP1, absent in melanoma-2 (AIM-2), caspase-4 and -8 which were mostly found during dsRNA virus or bacteria infection. The existing anti-inflammasome inhibitors for other non-infectious diseases were transferred to treat severe SARS-CoV-2 complications and have showed some encouraging results. This review highlights all reported inflammasomes involved in SARS-CoV-2 infection and the latest progress toward the development of therapeutics targeting them including NLRP3- and Gasdermin D (GSDMD)-inhibitors as well as other strategies such as immunomodulators and siRNA. Multiple inflammasomes exist in vivo and there is more than one way to make IL-1 during infection, blocking one inflammasome by its inhibitor may not affect the level of innate immune against the virus and thus does not increase risk of infection. Thus, to develop anti-inflammasome inhibitor holds a promise to treat severe COVID-19 syndrome effectively and reduce mortality.